Prevalence of Refractive Errors and their Association with Screen Time in School-Going Children: A Cross-Sectional Study - Muhammad Rizwan, Sarfraz Ahmad Mukhtar, Zulfiqar Ali, Abdullah Bin Zubair, Kashaf Rafi, Sana Azam, (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Refractive errors are a leading cause of visual impairment in children worldwide. With the increasing use of digital devices among school-aged children, concerns have emerged regarding the impact of prolonged screen time on eye health. Objective: To determine the prevalence of refractive errors in school-aged children and evaluate the association between screen time duration and the occurrence of these visual impairments. Methodology: A descriptive cross-sectional study was conducted at Sahiwal Teaching Hospital, Sahiwal, from 1st May 2023 to 1st October 2023. A total of 455 children aged 6 to 16 years from public and private schools were included using a non-probability consecutive sampling technique. Visual acuity was assessed using the Snellen chart, and children with subnormal acuity underwent further ophthalmologic evaluation. Results: Out of the 455 students examined, 162 (35.6%) were found to have refractive errors. Myopia was the most prevalent (19.6%), followed by hyperopia (9.5%) and astigmatism (6.6%). A statistically significant association was found between increased screen time and refractive errors (p < 0.001), with 50.9% of children having refractive errors in the >4 hours/day group compared to 22.6% in the <2 hours/day group. Refractive errors were more prevalent in private school students (42.4%) than in public school students (28.4%) (p = 0.002). No significant gender difference was observed (p = 0.64). Conclusion: Refractive errors are highly prevalent among school-going children and are significantly associated with prolonged screen time. The findings emphasize the need for regular vision screening, parental awareness, and promotion of healthy screen habits to mitigate visual health risks in children. Keywords: Refractive errors, myopia, screen time, visual impairment, digital eye strain.